(untitled) (Research, Society and Development, 2020)
This study aims to present the stages of production and execution of a didactic activity that can contribute to the learning of students in the 3rd year of high school. The intention is not just to be one more didactic material among the many existing ones, but it constitutes a work, that if used, can contribute to the appropriation of necessary skills to understand the financial and financial market operations existing in its daily life. The study was carried out 96 students and 66 teachers, where the following theories and methodologies were considered: didactic engineering, microgenetic analysis and the teaching of compound interest. Throughout the approach, care was taken to use elementary mathematics, thus facilitating its access to high school students. As a main result, the use of the didactic sequence was found to be favorable, as it enabled students to discover and construct concepts in Financial Mathematics, particularly compound interest.